Tailoring Microstructure and Superconducting Properties in Thick BaHfO3 and Ba2Y(Nb/Ta)O6 Doped YBCO Films on Technical Templates - Sieger, Max; Pahlke, Patrick; Lao, Mayraluna; Eisterer, Michael; Meledin, Alexander; Van Tendeloo, Gustaaf; Ottolinger, Rick; Haenisch, Jens; Holzapfel, Bernhard; Usoskin, Alexander; Kursumovic, Ahmed; Macmanus-Driscoll, Judith L.; et al. (IEEE Transactions on Applied Superconductivity, 2017)
The current transport capability of YBa2Cu3O7-x (YBCO) based coated conductors (CCs) is mainly limited by two features: the grain boundaries of the used textured template, which are transferred into the superconducting film through the buffer layers, and the ability to pin magnetic flux lines by incorporation of defined defects in the crystal lattice. By adjusting the deposition conditions, it is possible to tailor the pinning landscape in doped YBCO in order to meet specific working conditions (T, B) for CC applications. To study these effects, we deposited YBCO layers with a thickness of about 1-2 μm using pulsed laser deposition on buffered rolling-assisted biaxially textured Ni-W substrates as well as on metal tapes having either an ion-beam-textured YSZ buffer or an MgO layer textured by inclined substrate deposition. BaHfO3 and the mixed double-perovskite Ba2Y(Nb/Ta)O6 were incorporated as artificial pinning centers in these YBCO layers. X-ray diffraction confirmed the epitaxial growth of the superconductor on these templates as well as the biaxially oriented incorporation of the secondary phase additions in the YBCO matrix. A critical current density Jc of more than 2 MA/cm was achieved at 77 K in self-field for 1-2 μm thick films. Detailed TEM (transmission electron microscopy) studies revealed that the structure of the secondary phase can be tuned, forming c -axis aligned nanocolumns, ab-oriented platelets, or a combination of both. Transport measurements show that the Jc anisotropy in magnetic fields is reduced by doping and the peak in the Jc(θ) curves can be correlated to the microstructural features.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Alternating beam assisted deposition (ABAD); coated conductors; inclined substrate deposition (ISD); pinning; pulsed laser deposition; RABiTS; YBa